1998
DOI: 10.1080/10495399809525898
|View full text |Cite
|
Sign up to set email alerts
|

Multiple regions of the porcine α‐skeletal actin gene modulate muscle‐specific expression in cell culture and directly injected skeletal muscle

Abstract: Transcriptional regulation of the porcine alpha-skeletal actin gene was investigated by comparative transient transfection assays in cultured mammalian cells and by direct DNA injection in skeletal muscle. Intron I sequences were necessary to direct high-level, cell-specific porcine alpha-skeletal actin expression in C2C12 myotubes, but they inhibited transcription in skeletal muscle. A 5' distal sequence (-1929 to -550), had enhancer-like activity in C2C12 myotubes and directly injected muscle, and inhibited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
3
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 33 publications
4
3
0
Order By: Relevance
“…Of the non-viral promoters employed, some such as b actin have general activity within eukaryote cells. 30,31 Some promoters control expression in a cell-or tissue-specific manner eg a skeletal muscle actin promoter, 32 myosin light chain 3F promoter 33 and muscle creatine kinase (MCK) promoter 34 which are activated specifically in muscle. The best example of promoters of high cell specificity is the ventricle-specific myosin light chain-2 which is activated exclusively in cardiac myocytes.…”
Section: Promoter Enhancer and Other Elementsmentioning
confidence: 99%
“…Of the non-viral promoters employed, some such as b actin have general activity within eukaryote cells. 30,31 Some promoters control expression in a cell-or tissue-specific manner eg a skeletal muscle actin promoter, 32 myosin light chain 3F promoter 33 and muscle creatine kinase (MCK) promoter 34 which are activated specifically in muscle. The best example of promoters of high cell specificity is the ventricle-specific myosin light chain-2 which is activated exclusively in cardiac myocytes.…”
Section: Promoter Enhancer and Other Elementsmentioning
confidence: 99%
“…The porcine Sk-a-Act promoter, which contained ~1.9 kilobases (kb) of 5' DNA sequence (relative to the transcriptional start site), the first exon (55 bp), and 188 by of the first intron, was cloned 5' of luciferase cDNA to produce a 6.8 kb chimeric vector ( Figure 3). As previously reported (Reecy et al, 1998), this region of genomic DNA regulates the expression of porcine Sk-a-Act in a developmental and muscle specific manner. Although fibroblast contamination was never a significant problem in our primary cell culture model (data not shown), our luciferase promoter constructs were designed to retain muscle specific expression, which was conferred by an enhancer in the first intronic region (Reecy et al, 1998).…”
Section: Skeletal-a-actin Promoter Responsiveness To Ractopaminesupporting
confidence: 66%
“…As previously reported (Reecy et al, 1998), this region of genomic DNA regulates the expression of porcine Sk-a-Act in a developmental and muscle specific manner. Although fibroblast contamination was never a significant problem in our primary cell culture model (data not shown), our luciferase promoter constructs were designed to retain muscle specific expression, which was conferred by an enhancer in the first intronic region (Reecy et al, 1998). Initial transfection experiments in untreated C2C12 myotubes, C2C12 myoblasts, and 10T ~h fibroblasts confirmed that all constructs used in this study behaved in a developmental and tissue specific manner (data not shown).…”
Section: Skeletal-a-actin Promoter Responsiveness To Ractopaminesupporting
confidence: 66%
See 1 more Smart Citation
“…Direct injection of the DNA into skeletal muscle is an approach that has been successful in obtaining local expression of many recombinant proteins, such as chloramphenicol acetyl-transferase (Reecy et al 1998), luciferase (Manthorpe et al 1993), β-galactosidase (Wolff et al 1990), and dystrophin (Acsadi et al 1991). Draghia-Akli et al (1997) have injected DNA encoding growth hormone releasing factor into muscle and obtained increased circulating concentrations of growth hormone (GH) that affect body weight gain.…”
Section: Direct Dna Injectionmentioning
confidence: 99%